ANALISIS KEMAMPUAN KREATIVITAS MAHASISWA FISIKA FKIP UNRAM DENGAN BERBANTUAN MULTIREPRENSENTASI DESIGN TES DALAM PENGUASAAN MATERI GELOMBANG DAN OPTIK - Kosim Kosim; Hikmawati Hikmawati; Muh. Mahrus (Jurnal Penelitian Pendidikan IPA, 2019)
Research on student creativity at The Study Program of Physics Education FKIP Universitas Mataram for Wave and Optics course was conducted. This study aims to describe student creativity in the creativity of solving problems related to wave and optical matter. Tests were given to 21 students as samples with a test format following the principle of multi-representation on wave and optical questions. This test emphasizes the creativity of students' cognitive thinking which includes fluency, flexibility, originality, and elaboration. The results of cognitive thinking creativity in problem solving creativity showed that 38% were good and 68% were quite. Thus the mapping of the level quality of cognitive thinking creativity the students of Physics Education at FKIP Unram in the odd semester of the 2018/2019 academic year is generally at the level of being quite creative.Keywords: cognitive thinking creativity,  multi-representation